ANALISIS BEBAN PENCEMAR DAN IDENTIFIKASI SUMBER PENCEMAR AIR DARI SUMBER INSTITUSI DI KOTA BANJARMASIN - Aditya Rahman KN (Universitas Sultan Ageng Tirtayasa, 2015)
Wastewater point sources in Banjarmasin include of industrial activities, hotels, hospitals, restaurants and domestic waste. To the present, amount of pollutant load, types of point source water contaminants in Banjarmasin have not been inventored and properly identified. The purpose of this study was to inventory and identify pollutant point sources of water in an attempt to control water pollution in Banjarmasin. The research methods refer to Permen LH No. 1 of 2010 on the governance of water pollution control. Based on the governor’s quality standards No. 36 of 2008 of South Kalimantan, The Studied showed that large or small load of water pollutants is influenced by the presence or absence WWTP systems, types and levels of liquid waste emissions generated , as well as the capacity of the sources of pollution . From the results of the identification of many sources of water pollution from point sources environment parameter especially restaurants and hospitals exceed, the threshold quality standards established.